Humanist Fiqh Developed by KH. Ahmad Rifa’i Arief Banten, Indonesia - Ahmad Rajafi; Ressi Susanti; Ahmad Elmawan M. Alhanif (Institut Agama Islam Negeri Batusangkar, 2023)
This study aimed to examine the patterns and models of humanist fiqh developed by KH. Ahmad Rifa’i Arief through the popular boarding school in Banten, Indonesia, using a qualitative method. Data was obtained through observation, documentation, and comprehensive interviews, which were then analyzed using a descriptive approach. The results showed that KH. Ahmad Rifa’i Arief employed a philosophical approach in constructing the humanist fiqh, implemented across various Islamic Boarding Schools, including La Tansa. Furthermore, this approach emphasized the initial inward transformation (qalbi) as a means of self-introduction, subsequently imparting knowledge (qauli) and teaching, as well as culminating in tangible actions (fi’li) that benefit individuals regardless of their gender or social status.